Leroy Clarke entre poésie et peinture, Chantre de la spiritualité et de la liberté - Patricia Donatien-Yssa (Revue LISA)
The Trinidadian painter Leroy Clarke is hungry for art, and every piece of paper becomes under his fingers a field of experimentation for his excessive and impressive style. This anti-colonialist activist is also a Shango Baptist priest and in his conception of writing and painting, art cannot be an individualist exercise but is a space for communication with his people.This famous Caribbean painter practices an art whose strong symbolism finds its origin in the Shango Baptist faith which is one the bases of his work. But Leroy Clarke hates limits and cannot conceive being restricted to only one form of art; for painting, poetry or dance are all only the vectors of messages from the spirits. Painting and writing are, for Clarke, ritual acts of sublimation of the original and historical suffering of the Caribbean peoples, which transform the unspeakable and the unbearable into aesthetic realizations.So, in Clarke’s works, signs, words, traces and colours are organised in an identical dynamic of accumulation, correspondence and swarming which place the observer in an interstice outside time and space where he can be immersed in an embracing plenitude.